Megan Brandow-Faller. The Female Secession: Art and the Decorative at the Viennese Women’s Academy. Penn State UP, 2020. - Christa Spreizer (Studies in 20th & 21st Century Literature, 2023)
Review of Megan Brandow-Faller. The Female Secession: Art and the Decorative at the Viennese Women’s Academy. Penn State UP, 2020. 304 pp.
Keywords: Vienna; modernism; Secession; arts and crafts; feminism; women' s academy; women artists